Start smart - science I need to know. Understanding forces and Newton's 3 laws [videorecording (DVD)]. (Start smart. Science I need to know., 2014)
Understand the forces around and how friction, gravity, electromagnetism, and the atom play an integral role. Newton's three laws of motion are presented and explained in detail. Program is designed to reinforce and support the viewer's comprehension and retention of these terms through use of video footage, photographs, diagrams, and colorful, animated graphics and labels. See and hear the terms used in a variety of contexts, providing a model for how to appropriately use the words.